ANALISIS ATRIBUT OPINION LEADERSHIP YANG DIPERTIMBANGKAN OLEH PEMILIH PEMULA DALAM PEMILIHAN PRESIDEN (PILPRES) 2015 DI JAWA TIMUR - Inggrid Wiono Putri (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
Presindetial elections is one of political marketing in Indonesia. Political marketing is an alternative way of influencing political climate to gain greater support for the parties or presindent candidates. Many political parties use opinion leader in their campaign strategy. Opinion leader is a person who has ability to influence the opinions of others. This study analyzes what attributes really describe the opinion leader. The sample that are used in this study are 200 respondents aged between 17-21 years in East Java and participate in the presidential election voting for the first time. Sampling technique employed nonprobability sampling with judgment sampling method. The analytical technique that was used is Exploratory Factor Analysis (EFA). The result of this study indicates that the 9 factors formed 6 new factors that describe the opinion leadership accurately, namely ‘Inspiring’, ‘Reliable’, ‘Trusted’, ‘Learned’, ‘Mediator’, and ‘Experienced’.